Resiliensi Akademik pada Mahasiswa Fresh Graduate - Indriani, Jayanti; Soeharto, Triana Noor Edwina Dewayani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The transition to college presents new students with various academic and social demands that can potentially increase stress levels and hinder the adaptation process. Academic resilience is a crucial factor in helping students navigate these challenges, but empirical findings on the factors influencing it are scattered across studies. This study aims to synthesize empirical evidence on the factors influencing new students' academic resilience. The study employed a literature review with thematic content analysis of nine empirical studies obtained from Google Scholar, PubMed, and Scopus databases. Articles were selected through a screening process based on inclusion criteria: empirical research published between 2016 and 2026, discussing new students' academic resilience, available in full text, and relevant to the research objectives. Articles that did not meet these criteria were excluded from the analysis. The study's findings indicate that academic resilience is influenced by internal factors, such as self-efficacy, emotional regulation, optimism, self-determination, and social intelligence, as well as external factors such as support from family, lecturers or mentors, and peers. These findings confirm that strengthening personal factors and social support is an important strategy for increasing the academic resilience of new students, while also providing a basis for universities to design mentoring programs and academic services that support successful studies in the first year